Value of Thromboelastography for Condition Assessment in Children with Mycoplasma Pneumoniae Pneumonia - Jingjing GUI, Aquan JIN, Yu WAN, Xuan ZHAO, Linjie ZHU, Yidong ZHAO, Jiaqi YAO, Liwen ZHANG, Zhiying HUANG (Zhongguo quanke yixue, 2022)
Background Mycoplasma pneumoniae pneumonia (MPP) can cause a variety of intrapulmonary and extrapulmonary injuries, including thrombotic diseases, which seriously endanger the health of children. And for assessing the coagulation status, routine coagulation parameters has great limitations, while thromboelastography (TEG) can be comprehensively and rapidly, but there are few data on TEG used in condition evaluation in children with MPP. Objective To explore the value of TEG in condition assessment of children with MPP. Methods Two hundred and twelve MPP children were recruited from the Affiliated Changzhou No.2 People's Hospital of Nanjing Medical University from July 2019 to July 2021, including 52 with severe condition and 160 with non-severe condition. Comparisons were made between two groups in terms of demographics, platelet count, routine coagulation parameters, and TEG parameters. The association of TEG parameters with platelet count and routine coagulation parameters was assessed. Multivariate Logistic regression analysis was used to explore influence factors for the condition of MPP. ROC analysis was used for assess the value of those identified risk factors for predicting the condition of MPP. Results Both groups had no significant differences in sex ratio and mean age (P>0.05) . Compared with children with non-severe condition, those with severe conditionhad shortened reaction time (R) and kinetic time (K) , and elevated maximum amplitude (MA) , α-angle, clotting index (CI) , fibrinogen (FIB) , prothrombin time (PT) , international normalized ratio (INR) , D-dimer (D-D) (P<0.05) . Correlation analysis showed that MA was moderately positively associated with PLT and FIB (P<0.001) ; R was weakly positively associated with activated partial thromboplastin time (P<0.001) ; K was weakly negatively associated with PLT and FIB (P<0.001) ; α-angle was weakly positively correlated with PLT and FIB (P<0.001) . Multivariate Logistic regression analysis showed that CI〔OR=5.698, 95%CI (3.329, 9.753) , P<0.05〕, and D-D〔OR=5.061, 95%CI (1.724, 14.859) , P<0.05〕were influence associated with MPP, and the prediction algorithm based on them for MPP is CI+D-D: Y=1.777CI+1.624D-D-5.264. ROC analysis indicated that the area under the ROC curve of CI was 0.885〔95%CI (0.830, 0.941) 〕with 0.750 sensitivity and 0.907 specificity when the cut-off value was determined as 2.05, and that of D-D was 0.716〔95%CI (0.632, 0.799) 〕with 0.615 sensitivity and 0.784 specificity when the cut-off value was determined as 0.545, and that of CI in combination with D-D was 0.901〔95%CI (0.850, 0.952) 〕with 0.769 sensitivity and 0.914 specificity when the cut-off value was determined as -0.65. Conclusion TEG could partially predict the condition of children with MPP, but could not replace the routine coagulation parameters, and the combined predictive value of the two may be higher.